The Role of Self-Efficacy as a Mediator in the Relationship between Family Social Support and Resilience of Thesis-Writing Students at an Islamic State University - Arlotas, Rena Kinnara; Ruaidah, Ruaidah; Febrianti, Ariska; Putra, Rahman Pranovri (International Journal of Islamic Educational Psychology, 2026)
Resilience is an important psychological capacity for students in the thesis writing phase, as this phase is often accompanied by high academic pressure and psychological stress. This study aims to examine the effect of family social support on student resilience, with self-efficacy as a mediator. This study usedquantitative study with an ex-post facto approach. The participants in this study were 335 students who were writing their theses. The sampling technique used wasproportionate stratified random sampling. The instruments used in this study include the Family Social Support Scale, Self-Efficacy Scale, andDispositional Resilience Scale. Data analysis was conducted using simple regression analysis and mediation regression. The results showed that family social support had a significant effect on self-efficacy (p = 0.002 < 0.05), self-efficacy had a significant effect on resilience (p = 0.009 < 0.05), and family social support had a significant effect on resilience (p = 0.023 < 0.05). In addition, the results of the mediation analysis showed that self-efficacy fully mediated the relationship between family social support and resilience. This finding indicates that the higher the family social support, the stronger the student's self-efficacy, which ultimately increases the student's resilience in facing pressure and challenges during the thesis writing process.